(3GdMeGSI GdHUQjIs - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3GdeOQSI GdebOeI HOeTb s)
(3ChdgG (B:s
(3gPG eG GNJGQg CHh JeGe MHjH Hf ChS ef GdMeGSI hgj GdTLGYI HGH GdMeGSI hbGd HYV TYQGA HdYfHQ ai GdHSjW dh cfJ ef eGRf de JSJHM s
(3BNQgG (B:s
(3cCfeG dHSJ Ch CdHSJ afcG abdUJ ef MhGTjg Ydi GdShb Je GNJjGQ CHh JeGe MHjH Hf ChS GdWGFi s
(3GdfSNI HgG MhGTs
(3HChdg Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
Keywords: (3GdCOHs